Elimination of the J–V hysteresis of planar perovskite solar cells by interfacial modification with a thermo-cleavable fullerene derivative. Issue 45 (4th November 2016) - Xu, Qian; Lu, Zhen; Zhu, Lifeng; Kou, Chun; Liu, Yahui; Li, Cuihong; Meng, Qingbo; Li, Wenhua; Bo, Zhishan
Abstract : Efficient hysteresis elimination and significant performance improvement are achieved by interfacial modification with a thermo-cleavable fullerene derivative. Abstract : A thermo-cleavable fullerene derivative was used as an interfacial engineering material in planar perovskite solar cells. The modified TiO2 surface shows exceptional resistance against polar solvent washing and the perovskite film grown on it was of high quality with less pinholes. Consequently, high performance devices without hysteresis have been achieved.